AUTOMATION OF POWER FLUXES CONTROL IN ELECTRIC ENERGY SYSTEMS BY MEANS OF CROSS-TRANSFORMERS AND OPTIMUM MODES SIMILARITY - Lezhnyuk, Petro; Ngoma, Jean-Piere; Kilimchuk, Anton (Scientific Works of Vinnytsia National Technical University, 2015)
The paper considers the problem transversal-longtitudinal regulation of power fluxes and voltage in electric networks using cross-transformers and autotransformers as the problem of automatic control, the aim of it is formation of optimum control law and creation of corresponding system of automatic control. The given problem is solved on the basis of EES modes similarity and using criterial modes similarity and using criterial relations between their parameters.